Investment Analysis at PT Asuransi Takaful Keluarga against Optimal Portfolio - Selvia Selvia; Nur Ahmadi Bi Rahmani; Kusmilawaty Kusmilawaty (Journal La Sociale, 2024)
This article aims to determine the development of investment and which type of investment is optimal at PT Asuransi Takaful Keluarga. Qualitative and quantitative approaches are used in this research. The author in this case uses a linear program Excel solver maximizing returns to analyze investment development and analyze which type of investment is the most optimal at PT Asuransi Takaful Keluarga in 2020-2022. The investment tools used include mudarabah deposits, sukuk (Sharia Bonds), mutual funds, murabahah financing and stocks. The results of the analysis show that investment development has increased and decreased in each year and at PT Asuransi Takaful Keluarga has the optimal type of investment, namely Mudarabah deposits and sukuk.